2007
DOI: 10.1016/j.coph.2007.10.010
|View full text |Cite
|
Sign up to set email alerts
|

The leptin hypothesis of depression: a potential link between mood disorders and obesity?

Abstract: SummaryThe adipose-derived hormone leptin is well known for its function in the control of energy homeostasis. Recent studies suggest a novel role for this adipokine in the regulation of mood and emotion. Low levels of leptin have been found to be associated with depressive behaviors in rodents and humans. Pharmacological studies indicate that leptin has antidepressant-like efficacy. Both leptin insufficiency and leptin resistance may contribute to alterations of affective status. Identifying the key brain reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
198
3
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(226 citation statements)
references
References 62 publications
13
198
3
4
Order By: Relevance
“…In Alzheimer's disease, the hippocampus is one of the first regions of the brain to suffer damage; memory problems and disorientation appear among initial symptoms [24,31]. It has been shown that leptin facilitates spatial learning and memory [14][15][16] and that it produces antidepressant-like effects [17][18][19][20][21][22]. It has also been proposed that high levels of leptin are associated with lower rates of dementia and Alzheimer's disease [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Alzheimer's disease, the hippocampus is one of the first regions of the brain to suffer damage; memory problems and disorientation appear among initial symptoms [24,31]. It has been shown that leptin facilitates spatial learning and memory [14][15][16] and that it produces antidepressant-like effects [17][18][19][20][21][22]. It has also been proposed that high levels of leptin are associated with lower rates of dementia and Alzheimer's disease [31].…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings demonstrate that leptin facilitates spatial learning and memory [14][15][16] and produces antidepressantlike effects [17][18][19][20][21][22]. Amylin has a beneficial effect on the CNS to alter physiological responses to feeding [23].…”
Section: Introductionmentioning
confidence: 99%
“…Recently significant interest has arisen in possible interactions between central mood substrates and circuitries involved in metabolism (Gomez-Pinilla, 2008;Krishnan and Nestler, 2008;Kuperman et al, 2010;McBriar, 2006;Shao et al, 2008). More specifically, several neuropeptides with a clear role in metabolism, such as leptin, ghrelin, orexin, neuropeptide Yand urocortin 3, produce clear anti-depressant-like responses (Eaton et al, 2007;Heilig, 2004;Kuperman et al, 2010;Lu, 2007;Lutter et al, 2008;Yamada et al, 2011), whereas e.g. melanin-concentrating hormone and cholecystokinin evoke a pro-depressant-like phenotype in several rodent models (Becker et al, 2008;Georgescu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found a social gradient in both work stress and metabolic syndrome (41)(42)(43), suggesting that the social gradient in metabolic syndrome and heart disease may be partly explainable by greater exposure to work stress Table 1 Means, standard deviations, Cronbach's Alpha and interscale correlations (n = 79) among less advantaged social groups. Metabolic syndrome and obesity have also been linked to several other psychological factors: body dissatisfaction, self-esteem, depression (44)(45)(46), stress (47)(48)(49), and positive and negative affect (50)(51). In line with previous reports, our study revealed that, in comparison with controls, overweight participants had significantly higher values of depression (6.75 ± 2.87 vs. 4.93 ± 3.32, P < 0.05) and anxiety (7.33 ± 2.68 vs. 6.03 ± 2.92, P < 0.05), and lower levels of optimism (15.13 ± 3.69 vs. 17.85 ± 3.95, P < 0.01) and satisfaction with life (21.49 ± 5.77 vs. 24.70 ± 6.80, P < 0.05).…”
Section: Discussionmentioning
confidence: 99%